Penegakan Hukum Terhadap Penyelenggaraan Pasar Tradisional Oleh Pengelola Pasar Tanpa Lahan Parkir - Mohede, Noldy; Dapu, Frits Marannu; Pinasang, Boby (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The existence of traditional markets has had a positive impact on the welfare of the community. However, its development has an impact on the need for adequate and safe parking facilities for all market users. This study aims to determine how law enforcement is carried out on the management of traditional markets without parking lots. In today's era, the role of markets is very central to the national economy. This normative empirical study concludes that the management of parking lots in traditional markets at the research location still requires more intensive law enforcement so that it can reduce friction between market parking users, including road users. This requires consideration of the fulfillment of 5 law enforcement factors so that its management is in accordance with the law and fulfills a sense of justice for all parties.